Training of Trainers (ToT) Report on Rice-Fish Suitability Decision Support System Modelling, Myanmar - Moet, Palal (2023)
IWMI Myanmar team and a group of consultants conducted comprehensive five days TOT training on “Rice-Fish Suitability Decision Support System Modelling” to support the capacity development of potential national experts/staffs from three government departments – Land Use Division, Department of Agriculture (DOA), Department of Planning (DOP), and Department of Fisheries (DOF) under the same Ministry of Agriculture, Livestock and Irrigation (MOALI) based in Naypyidaw. The idea is that the trainers from DOA/DOF are to train the DOA/DOF staff from Ayeyarwady region, being monitored and assisted by the IWMI training team.